2019
DOI: 10.21873/anticanres.13572
|View full text |Cite
|
Sign up to set email alerts
|

P53/MDM2 Co-Expression in Laryngeal Squamous Cell Carcinoma Based on Digital Image Analysis

Abstract: Background: P53 is a key regulator of genomic stability and function, acting as a tumor suppressor protein. Our aim was to correlate P53 expression with murine double minute 2 (MDM2), a proto-oncogene that interacts with P53 and forms an auto-regulatory pathway, in laryngeal squamous cell carcinoma (LSCC). Materials and Methods: A total of 50 LSCC cases were included in the study. Immunohistochemistry was applied by using antibodies to P53 and MDM2 in the corresponding tissue sections. Protein expression level… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 28 publications
0
7
0
Order By: Relevance
“…Sendtner et al [14] found that upregulation of LIF significantly increased nutritional and physiological related effects on motoneurons by cotransfection of CNTF and LIF genes. Chrysovergis et al [23] also proved that double-gene integration promoted the expression of target genes in laryngeal squamous cell carcinoma. The reason may be related to the gene regulatory network in the organism and the complex and multilevel regulation of gene expression.…”
Section: Discussionmentioning
confidence: 97%
“…Sendtner et al [14] found that upregulation of LIF significantly increased nutritional and physiological related effects on motoneurons by cotransfection of CNTF and LIF genes. Chrysovergis et al [23] also proved that double-gene integration promoted the expression of target genes in laryngeal squamous cell carcinoma. The reason may be related to the gene regulatory network in the organism and the complex and multilevel regulation of gene expression.…”
Section: Discussionmentioning
confidence: 97%
“…For the past few years, many biomarkers have been applied for the diagnosis and treatment of LSCC (Cossu et al, 2019). Various anti-LSCC mechanisms have also been identified (Chrysovergis et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…In addition, a recent study recorded that cytochrome P450 inhibited the activity of the metabolic enzymes CYP2C9 Ã 2 and CYP2C9 Ã 3, which could directly control tumorigenesis by reducing epoxyeicosatrienoic acid production (Hunter et al, 2015;Katiyar et al, 2017). The PI3K-Akt signalling pathway has a vital function in LSCC by suppressing cell death (Chrysovergis et al, 2019;Yang et al, 2019). P53, a tumour suppressor factor, initiates DNA repair, cell cycle arrest and apoptosis and reacts to various kinds of cancer therapies (Cui, Qu & Liu, 2019;Ragos et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, p53 expression, together with Mouse double minute 2 homolog expression (MDM2), was positively correlated with advanced stage of LSCC by Chrysovergis et al, as demonstrated by immunostaining of p53 and MDM2 in the 50 LSCC patients included in their study. The results showed p53 overexpression in 32% LSCC patients and a stronger MDM2 expression in 44% cases [ 33 ]. TP53 gene mutations have been also assumed to affect the response to radiotherapy and drive both cell differentiation and neck LNM, although no correlation with LSCC clinical stages was observed [ 34 , 35 ].…”
Section: Molecular Markers For Clinical Management Of Lsccmentioning
confidence: 99%